Decitabine treatment in 311 patients with acute myeloid leukemia: outcome and impact of TP53 mutations – a registry based analysis. Issue 6 (12th May 2021) - Middeke, Jan M.; Teipel, Raphael; Röllig, Christoph; Stasik, Sebastian; Zebisch, Armin; Sill, Heinz; Kramer, Michael; Scholl, Sebastian; Hochhaus, Andreas; Jost, Edgar; Brümmendorf, Tim H.; Naumann, Ralph; et al.
Abstract: We performed a registry-based analysis of 311 AML patients treated with decitabine in a standard of care setting to assess response and survival data with a distinct focus on the impact of the TP53 mutation status. Median age was 73 years. 172 patients received decitabine first-line and 139 in r/r disease. The ORR (whole cohort) was 30% with a median overall survival of 4.7 months. First-line patients achieved better responses than r/r-patients (ORR: 38% vs. 21%) resulting in a median OS of 5.8 months vs. 3.9 months. NGS based mutation analysis was performed in 180 patients. 20 patients (11%) harbored a TP53 mutation. Response rates and survival did not differ significantly between TP53 mutated patients and wild-type patients. This analysis of a large cohort of AML patients provides response rates and OS data after decitabine treatment. Interestingly, outcome was not negatively influenced by a TP53 mutation.